LEXICAL-SEMANTIC PECULIARITIES OF URBAN PLANNING TERMINOLOGICAL UNITS IN LSP (Conferencea, 2023)
The article studies semantic peculiarities of urban planning terminological units in ESP classes, the phenomena of antonymy, synonymy, duplication, variance. Terminological phrases of the scientific and technical field "urban planning" in the special vocabulary of English language.